The Controversial Effect of Age on Divergent Thinking Abilities: A Systematic Review. (23rd June 2020) - Fusi, Giulia; Lavolpe, Sara; Crepaldi, Maura; Rusconi, Maria Luisa
Abstract: Divergent thinking (DT) is considered as an indicator of creative potential and a predictor of creative achievement. Furthermore, it is also conceptualized as an indicator of cognitive reserve (CR) in healthy elderly. CR refers to a functional benefit that can potentially offer protection against brain pathologies and is thereby considered a protective factor against cognitive decline. Creativity researchers have therefore attempted to understand the impact of the aging processes on DT abilities; however, it is difficult to draw a coherent picture from these studies. The aim of our systematic review was to more consistently summarize and interpret evidence about this topic. We selected 16 studies using the Preferred Reporting Items for Systematic reviews and Meta‐Analyses (PRISMA) guidelines. Our findings highlight a complex and multidimensional, rather than a simple linear relationship between the aging processes and DT performances, especially if the different DT indexes are considered separately. We also found that findings from more recent studies suggest that older subjects are able to think as divergently as younger people, particularly in the verbal domain, if no time constraints are imposed and if the workload is not too high. We conclude by discussing theoretical and methodological issues and implications for future research.